Associations of Work Hours and Actual Availability of Weekly Rest Days with Cardiovascular Risk Factors. Issue 1 (2nd April 2013) - Itani, Osamu; Kaneita, Yoshitaka; Ikeda, Maki; Kondo, Shuji; Murata, Atsushi; Ohida, Takashi
Abstract : Associations of Work Hours and Actual Availability of Weekly Rest Days with Cardiovascular Risk Factors: Osamu ITANI, et al . Division of Public Health, Department of Social Medicine, Nihon University School of Medicine— Objectives: The aim of study was to determine the associations of work hours and actual availability of weekly rest days with the onset of lifestyle‐related diseases such as obesity, hypertension, hypertriglyceridemia, low levels of high‐density lipoprotein (HDL) cholesterol and hyperglycemia. Methods: For this longitudinal study, we used data from checkups conducted in 1999 and 2006 for 30, 194 men who worked for a local public institution in Japan. We calculated the cumulative incidence rates of onset of obesity, hypertension, hyperglycemia, hypertriglyceridemia and low HDL cholesterol over this 7‐year period and performed a χ 2 test to determine the association between the above diseases and work conditions (work hours and actual availability of weekly rest days) at the time of the baseline survey. We then performed multiple logistic regression analysis of the diseases that showed significant associations. Results: The adjusted odds ratio for the onset of hypertriglyceridemia in subjects who worked ≥9 hours was high (1.11 [95% CI: 1.02−1.22], p =0.02) in comparison with those who worked <9 hours. The adjusted odds ratio for the onset of hypertriglyceridemia in subjects who could not often take weekly rest days was high (1.13 [95% CI: 1.01−1.27], p =0.03) in comparison with those who were able to take most of the available weekly rest days off work. Conclusions: These results show that work hours and actual availability of weekly rest days independently predict the onset of hypertriglyceridemia. Working only regular hours and taking advantage of weekly rest days can contribute to the prevention of hypertriglyceridemia.